Protective Effects of Pyridoxamine Supplementation in the Early Stages of Diet-Induced Kidney Dysfunction. (29th October 2017) - Chiazza, F.; Cento, A. S.; Collotta, D.; Nigro, D.; Rosa, G.; Baratta, F.; Bitonto, V.; Cutrin, J. C.; Aragno, M.; Mastrocola, R.; Collino, M.
Abstract : Pyridoxamine, a structural analog of vitamin B6 that exerts antiglycative effects, has been proposed as supplementary approach in patients with initial diabetic nephropathy. However, the molecular mechanism(s) underlying its protective role has been so far slightly examined. C57Bl/6J mice were fed with a standard diet (SD) or a diet enriched in fat and fructose (HD) for 12 weeks. After 3 weeks, two subgroups of SD and HD mice started pyridoxamine supplementation (150 mg/kg/day) in the drinking water. HD fed mice showed increased body weight and impaired glucose tolerance, whereas pyridoxamine administration significantly improved insulin sensitivity, but not body weight, and reduced diet-induced increase in serum creatinine and urine albumin. Kidney morphology of HD fed mice showed strong vacuolar degeneration and loss of tubule brush border, associated with a drastic increase in both advanced glycation end products (AGEs) and AGEs receptor (RAGE). These effects were significantly counteracted by pyridoxamine, with consequent reduction of the diet-induced overactivation of NF-kB and Rho/ROCK pathways. Overall, the present study demonstrates for the first time that the administration of the antiglycative compound pyridoxamine can reduce the early stages of diet-dependent kidney injury and dysfunction by interfering at many levels with the profibrotic signaling and inflammatory cascades.